ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA HINDU SETELAH PEMBELAJARAN MASA PANDEMI COVID-19 - putu, widiyanto (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2023)
Learning during the Covid 19 pandemic has made face-to-face learning methods into learning from home. This condition certainly makes a change from how the teacher teaches, materials to the learning tools used. It is feared that this change in conditions will have an impact on the achievement of students' critical thinking skills. This study aims to determine the impact of learning during the Covid-19 pandemic on the critical thinking skills of Hindu students at SDN 1 Sidorejo Tamban Catur, Kapuas Regency. This research was carried out by distributing instruments in the form of written tests to 17 students in grade 5. The data obtained from the written test will be analyzed based on indicators of critical thinking skills. The findings in the field showed that 52.9% of grade 5 students at SDN 1 Sidorejo Tamban Catur Kapuas Regency had very high critical thinking skills after learning was carried out from home during the Covid 19 pandemic